Enabling the Use of Alkyl Thianthrenium Salts in Cross‐Coupling Reactions by Copper Catalysis. Issue 40 (26th August 2021) - Chen, Cheng; Wang, Minyan; Lu, Hongjian; Zhao, Binlin; Shi, Zhuangzhi
Abstract: Alkyl groups are one of the most widely used groups in organic synthesis. Here, a a series of thianthrenium salts have been synthesized that act as reliable alkylation reagents and readily engage in copper‐catalyzed Sonogashira reactions to build C(sp 3 )−C(sp) bonds under mild photochemical conditions. Diverse alkyl thianthrenium salts, including methyl and disubstituted thianthrenium salts, are employed with great functional breadth, since sensitive Cl, Br, and I atoms, which are poorly tolerated in conventional approaches, are compatible. The generality of the developed alkyl reagents has also been demonstrated in copper‐catalyzed Kumada reactions. Abstract : A series of thianthrenium salts have been developed that can undergo C(sp 3 )−S bond cleavage and be used as reliable alkyl reagents. This ability has been demonstrated in copper‐catalyzed Sonogashira and Kumada cross‐coupling reactions under mild conditions.